How successful are oncologists in identifying patient distress, perceived social support, and need for psychosocial counselling? - Söllner, W (Nature Publishing Group, 2001)
20–40% of cancer patients show emotional distress. Psychosocial support should be offered to severely distressed patients. However, little is known about the selection of patients to whom such support should be offered. This study investigated oncologists' ability to identify such patients. In a consecutive series of 298 cancer patients undergoing radiotherapy, distress, perceived social support and desire for supportive counselling were assessed using screening instruments. Simultaneously, 8 oncologists estimated patient distress and need for psychosocial support. A complete set of data was obtained in 80.2% of cases. Concordance of the oncologists' estimation of patient distress and perceived social support with the results of the screening instruments was weak (κ = 0.10 and κ = 0.05). Oncologists recognized the presence of severe distress only in 11 of the 30 severely distressed patients. Correct perception of distress was lower in patients with head and neck cancer and lung cancer and in lower class patients. Oncologists' recommendations for supportive counselling did not correlate with patient distress or the amount of perceived support but rather with progressive disease and less denial behaviour. Our results underline the need for educating oncologists in order to improve their ability to identify patient distress. © 2001 Cancer Research Campaign http://www.bjcancer.com